Shift From Coke to Coal Using Direct Reduction Method and Challenges - Chukwuleke, Okonkwo Paul; CAI, Jiu-ju; Chukwujekwu, Sam; XIAO, Song (Journal of iron and steel research, international, 2009)
Ironmaking involves the separation of iron ores. It not only represents the first step in steelmaking but also is the most capital-intensive and energy-intensive process in the production of steel. The main route for producing iron for steelmaking is to use the blast furnace, which uses metallurgical coke as the reductant. Concerns over the limited resources, the high cost of coking coals, and the environmental impacts of coking and sinter plants have driven steelmakers to develop alternative ironmaking processes that can use non-coking coals to reduce iron ores directly. Since the efficiency and productivity of modern large capacity blast furnaces will be difficult to surpass, blast furnaces will continue to retain their predominant position as the foremost ironmaking process for some time to come. The alternative ironmaking processes are therefore expected to play an increasingly significant role in the iron and steel industry, especially in meeting the needs of small-sized local and regional markets. It is likely that the importance of direct reduced iron (DRI) and hot metal as sources of virgin iron will continue to increase, especially in the developing countries where steelmaking is, and will be, primarily based on electric arc furnace (EAF) minimills. Consequently, the challenges that are faced by the new technology have to be embraced.